Faktor-Faktor Yang Berhubungan Dengan Ketidakpatuhan Kontrol Penderita Hipertensi - Madarina; Faridah Hanum; Rosi Noviyanti (Jurnal Assyifa: Jurnal Ilmu Kesehatan Lhokseumawe, 2022)
Non-compliance with hypertension patients with hypertension control is not good. This one of them can cause blood pressure to become uncontrolled which will have an impact on the emergence of various kinds of complications. The purpose of the study was to determine the factors associated with non-adherence to control of hypertension sufferers. The design of this research is analytic, with a cross sectional approach. The population in this study were all patients with hypertension who received health services in June 2021 as many as 52 people. The number of samples as many as 52 respondents was determined by using the total sampling technique. The research was carried out on August 13 to 18, 2021. The analysis was carried out using a computerized process through the chi-square test. Based on the results of the study, it was found that the knowledge of hypertension sufferers was in the good category of 59.6%, the motivation of hypertension patients was in the good category of 61.5%, the family support of hypertension patients was in the good category of 57.7% and non-compliance with control of hypertension patients was in the obedient category of 69.2%. . The results of the p-value < = 0.05, this proves that there is a relationship between knowledge, motivation and family support with non-compliance with control of hypertension sufferers. It is expected that people with hypertension will regularly control their blood pressure according to doctor's recommendations so as to minimize the possibility of complications that can occur.